Fluctuating asymmetry as a predictor for rowing ergometer performance - Longman, D.; Stock, J. T.; Wells, J. C. K. (International Journal of Sports Medicine, 2011)
Fluctuating asymmetry (FA) can be defined as an organism's deviation from perfect bilateral symmetry. FA has been of interest to evolutionary biologists as it may be indicative of the ability of an individual to express its genotype in a stable manner. Asymmetry has been shown to correlate with success in both intra- and inter-sexual selection in various species, including humans. A growing body of knowledge is emerging concerning the relationship between asymmetry and sporting ability. This study seeks to expand upon understanding of developmental stability and athletics by investigating the association between asymmetry and performance in rowers. Both male and female competitors from a range of abilities were tested (76 males and 70 females), with asymmetry being determined through bilateral digit measurements and performance through personal best time over 2 000 m on the Concept 2 indoor rowing ergometer. Significant negative correlations were observed between asymmetry and 2 000 m ergometer performance in both males and females. The relationship remained significant after adjustment for rowing experience and height. These results suggest that asymmetry may serve as a predictor of potential ability in the sport of rowing. The cause for the association between asymmetry and sporting performance has yet to be identified.